Overcoming Implementation Barriers in a Qualitative Study of the Supplementary Feeding Program for Malnourished Toddlers in Rural Indonesia - Sri Wahyuni Nasution; Yerniyanti Lahagu; Chrismis Novalinda (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Nutritional problems among toddlers, particularly malnutrition, remain a significant public health concern in Indonesia. The Supplementary Feeding Program (PMT) is a key government initiative that utilizes local food resources to improve the nutritional status of children under five. However, the program continues to face several implementation challenges that must be addressed to ensure its effectiveness. This study aimed to identify the challenges and solutions associated with the implementation of the PMT in the Sei Mencirim Health Center area, Deli Serdang Regency. A qualitative case study design was employed, involving eight key informants comprising health workers, posyandu cadres, and parents of PMT recipients. Data were collected through in-depth interviews and analyzed thematically using the Miles and Huberman framework, which includes data reduction, data display, and verification. The findings revealed several key challenges: untimely distribution of PMT, declining food quality, budget constraints, low parental education levels, and limited parental involvement in program monitoring. To address these issues, a range of targeted solutions was implemented, including the formation of dedicated distribution teams, menu standardization, establishment of centralized food processing sites, improved data accuracy, continuous staff training, enhanced cross-sector coordination, and routine monitoring and evaluation. These interventions led to a 35% improvement in the timeliness of PMT distribution and a 50% increase in family participation, contributing positively to the nutritional outcomes of toddlers. In conclusion, targeted interventions and multisectoral collaboration significantly enhanced the effectiveness of PMT implementation in the study area. Keyword: Supplementary Feeding Program, Toddlers, Implementation Challenges, Nutritional Status, Qualitative Study.